Dr. Who?! capturing the life and times of a leader in cartoons - Lat Dato' 1951- (MPH Group Publishing, 2018)
Relevant and hilarious, this compilation of Lat's cartoons features the life and times of Tun Dr Mahathir Mohamad, the fourth and current Prime Minister of Malaysia. Datuk Mohammad Nor Khalid, more commonly known as Lat, is a Malaysian cartoonist. Winner of the Fukuoka Asian Culture Prize in 2002, Lat has published more than 20 volumes of cartoons since he was 13 years old. His works mostly illustrate Malaysia's social and political scenes, portraying them in a comedic light without bias. Lat's best known work is The Kampung Boy (1979), which is published in several countries across the world. In 1994, the Sultan of Perak bestowed the honorific title of Datuk on Lat, in recognition of the cartoonist's work in helping to promote social harmony and understanding through his cartoons.